Os Penis Fracture Resulting in Urethral Obstruction in a Dog: A Case Report - Kumar, Mahesh; Kumar Sahu, Uttam; Singh, Kiranjeet; Gopinathan, Aswathy; Kumar Yadav, Sanjay; Kumar KS, Kamalesh; Sai Kumar, T; L, Chandana (Animal Reproduction Update, 2025)
Fracture of the os penis (FOP) is a rare and underreported condition in dogs that can result in serious complications, including urethral obstruction. This report documents the clinical presentation, diagnosis, and successful surgical management of a 7-year-old male mongrel dog with urethral obstruction secondary to an os penis fracture. The dog presented with pollakiuria, dysuria, penile swelling, abdominal distension, and urinary dribbling. Clinical examination revealed a distended bladder and pain on urination, and catheterization was unsuccessful. Radiographic imaging (ventrodorsal and lateral views) confirmed a fracture of the os penis, while ultrasonography revealed urinary bladder distension and urethral dilation proximal to the fracture. Surgical correction involved scrotal urethrostomy and castration under general anaesthesia. Pre-medication included glycopyrrolate, diazepam, and butorphanol, followed by induction with propofol and maintenance with isoflurane. The urethral mucosa was sutured to the skin using non-absorbable polyamide 3-0 sutures, and a urinary catheter was placed to maintain patency. Postoperative recovery was uneventful, with restoration of normal urination and a reduction in serum creatinine to 1.2 mg/dL. This case highlights the importance of prompt diagnosis and surgical intervention in os penis fractures complicated by urethral obstruction.